On regularity of linear summation methods of Taylor series - Zaderey, P. V.; Gaevskij, M. V. (Methods of Functional Analysis and Topology, 2015)
The paper specifies necessary and sufficient conditions for regularity of an infinite matrix of real numbers, which determines some summation method for a class of functions that are analytic on the unit disk and continuous on the closed circle.